Corruption, Government, and the Educated Generation: A Social Impact Study from a Marxist Perspective - Pirana Rachma Sari; Sugeng Harianto (Dinasti International Journal of Education Management And Social Science, 2025)
Corruption in Indonesia is not merely a manifestation of individual moral failure, but rather a structural phenomenon rooted in an unequal social and political system. From the Marxist perspective of Karl Marx’s social conflict theory, corruption is understood as a tool of domination used by the ruling class to maintain control over resources and power. This study employs a qualitative approach through a literature review method to analyze the social impacts of corruption, particularly on governance structures and the future of the educated generation. The findings reveal that corruption systematically undermines the government’s function as a public servant by fostering an unaccountable and exclusive bureaucracy, thereby triggering social disintegration due to public distrust in the state. In the education sector, corruption exacerbates inequality and hampers social mobility, depriving younger generations of equal opportunities for advancement in a system that prioritizes power relations over meritocracy. Corruption not only results in material losses but also cultivates a permissive mindset toward injustice, posing a threat to human resource development. This study aims to formulate progressive and transformative social strategies to establish more just, transparent, and corruption-free governance and education systems.